Pharmacokinetic and pharmacodynamic studies of nicotine in rat brain: a simultaneous investigation of nicotine metabolites and the release of neurotransmitters in vivo - Guo, Lulu; Mao, Jian; Zhang, Qidong; Fan, Wu; Wang, Dingzhong; Li, Zhonghao; Huang, Jiaqiang; Xie, Jianping (Frontiers in Chemistry, 2023)
Introduction: The body’s ability to metabolize nicotine and the disposition of nicotine in the brain are important determinants of its exposure. Limited knowledge about the near real-time changes of neurochemicals during the brain nicotine metabolic process hinders the recognition of its multiple neuropharmacological effects. Methods: An online microdialysis coupled with UHPLC-HRMS/MS method for the in vivo multi-analysis of nicotine metabolites and several neurotransmitters in rat brain was developed. Whether the systemic modulation of metabolic enzyme CYP2B would modulate nicotine pharmacokinetics and local neurochemical effects was further investigated. Results: The dynamic profiles of over 10 nicotine metabolites and neurotransmitters were simultaneously obtained after a single injection of nicotine (2 mg·kg−1, i.p.) using the new method. Proadifen pretreatment (50 mg·kg−1·d−1, i.p., 4 days) caused significant inhibition of brain CYP2B1 activity. When exposed to nicotine, the brain Cmax of nicotine was 1.26 times higher and the levels of nicotine metabolites, nornicotine, and nicotine-N-oxide, were decreased by 85.3% and 34.4% in proadifen-pretreated rats. The higher level of brain nicotine induced a greater release of dopamine, serotonin, glutamate, and γ-amino-butyric acid in the nucleus accumbens. The concentrations of nicotine and dopamine were positively correlated, and the average levels of γ-amino-butyric acid and serotonin were 2.7 and 1.2 times higher, respectively, under the inhibition of nicotine metabolism. Discussion: These results demonstrated that inhibiting nicotine metabolism in rats can enhance the residence of brain nicotine and its local neurotransmitter effects. The metabolic activity of nicotine under different physiological conditions could regulate nicotine’s bioavailability and its resulting pharmacology.